2005
DOI: 10.3758/bf03193083
|View full text |Cite
|
Sign up to set email alerts
|

The perception of handshapes in American Sign Language

Abstract: Despite the constantly varying stream of sensory information that surrounds us, we humans can discern the small building blocks of words that constitute language (phonetic forms) and perceive them categorically (categorical perception, CP). Decades of controversy have prevailed regarding what is at the heart of CP, with many arguing that it is due to domain-general perceptual processing and others that it is determined by the existence of domain-specific linguistic processing. What is most key: perceptual or l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
46
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 47 publications
(65 reference statements)
8
46
0
Order By: Relevance
“…The outcome of the handshape identification task was consistent with earlier studies which found a similar sigmoidal function in deaf ASL signers and hearing non-signers (Baker, et al, 2005;Lane, Boyes-Braem, & Bellugi, 1976). In line with previous results, our findings suggest that linguistic experience does not mediate identification of visual features for the purpose of binary handshape categorization.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The outcome of the handshape identification task was consistent with earlier studies which found a similar sigmoidal function in deaf ASL signers and hearing non-signers (Baker, et al, 2005;Lane, Boyes-Braem, & Bellugi, 1976). In line with previous results, our findings suggest that linguistic experience does not mediate identification of visual features for the purpose of binary handshape categorization.…”
Section: Discussionsupporting
confidence: 92%
“…The increased discrimination accuracy for handshapes straddling category boundaries has previously been attributed to the perceived contrast between phoneme categories in speech (Liberman, et al, 1957;Liberman, et al, 1961) or in lexical signs in ASL (Baker, et al, 2005;Emmorey & Herzig, 2003). Baker et al (2005) …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The fourth study (Baker, Idsardi, Golinkoff, & Petitto, 2005) differed importantly from the other three in its use of nonsense stimuli rather than real signs; it also differed from Emmorey et al (2003) and the follow-up experiments of Newport (1982) by using dynamic video stimuli. Baker et al employed three handshape contrasts (A-vs. B-bar, as in Emmorey et al, 2003, as well as 5 vs. flat-O and 5 vs. S; see Figure 2A).…”
mentioning
confidence: 91%
“…Also, comparison of native versus nonnative lateonset deaf signers allowed assessment of ASL onset-age effects with hearing status held constant. 1 Given that both speech and signs have phonological structure, one hypothesis is that native phonological structure will affect perception of contrasts similarly by users Sign-naive participants allegedly lack categorical perception for all sign contrasts tested (dynamic, Baker et al, 2005;static, Emmorey et al, 2003).…”
mentioning
confidence: 99%